Meetings between experiences of being a child in São Paulo and São Gabriel da Cachoeira - Massagardi Caetano da Silva, Nadia; Santiago do Nascimeto, Ana Paula (Guará Journal, 2024)
This  paper  presents  the  actions  and  reflections  carried  out  in  the  project  “Correspondence  between  diff  erent  Brazilian  chil-dhood experiences” carried out in the years 2017 and 2018 with children from 4 to 6 years of age that involved teaching, the re-search and university extension in the exchange of correspon-dence between children of São Paulo - SP and São Gabriel da Cachoeira - AM. It was carried out through circles of conversa-tions and photographic and graphic records on the daily lives of  children  and  documentary  and  bibliographical  surveys  on  indigenous  communities  in  Brazil.  This  action  contributed  to  the  change  of  perspective  of  children  about  indigenous  peo-ples and the continuing education of educators involved in the process.
Keywords: Indigenous children; Young children; Childhood ex-periences; Education for ethnic-racial relations; University extension